Resource Use Efficiency (RUE) in Lentil Production in Terai and Inner Terai Regions of Nepal - Gautam, Damodar; Dhakal, Shiva Chandra; Kattel, Rishi Ram; Khanal, Narayan Prasad (Journal of Nepal Agricultural Research Council, 2022)
A study was carried out to estimate and analyze the profitability and resource use efficiency of lentil grain and seed production in Nepal's terai and inner terai regions. Using a pre-tested questionnaire, primary data and information were collected from 300 lentil grain producing farmers, categorized by local seed users, improved seed users, and 100 seed producing farmers in Kailali, Dang, and Siraha districts. The study revealed that the B:C ratio in lentil seed production was higher (1.59) than in lentil grain production (1.41). The benefit in both grain and seed production realized by farmers was mainly due to increased prices rather than production. Return to scale was found to be increasing (1.016) in lentil grain production using local seed, but it was decreasing at a rate in lentil grain production using improved seed (0.854) and in lentil seed production (0.822). Analysis on resource use efficiency revealed that labor input is excessively overused, reflecting the Marginal Value Product of less than unity in lentil production. To get the maximum profit from lentil grain production using improved seed, input use in land preparation, threshing, and post-harvest should be increased while decreasing the amount of other inputs.